Proceedings of the International Joint Conference on Science and Engineering 2022 (IJCSE 2022) 2022
DOI: 10.2991/978-94-6463-100-5_16
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Fuel Consumption in Four-Stroke Engines Using Nickel-Plated Copper Catalytic Converters

Abstract: This study aims to evaluate the ability of nickel-plated copper catalytic converters to the fuel consumption of a four-stroke engine. This experimental research uses Yamaha Vixion Lightning as the object of research. Research instruments used include chassis dynamometer, and fuel flow meter. Fuel consumption measurements are carried out based on SNI standard 7554:2010. Results from this study showed that the metallic catalytic converter's ability to fuel consumption on a four-stroke motorcycle is no better tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…These findings are supported by previous research. Warju et al [6] revealed that the use of honeycomb-structured catalysts can significantly reduce pollutant emissions from motor vehicles. This finding aligns with the results found by Patil and Chaudhary [26], which showed that increasing the catalyst surface area can enhance pollutant conversion efficiency while reducing vehicle power loss.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are supported by previous research. Warju et al [6] revealed that the use of honeycomb-structured catalysts can significantly reduce pollutant emissions from motor vehicles. This finding aligns with the results found by Patil and Chaudhary [26], which showed that increasing the catalyst surface area can enhance pollutant conversion efficiency while reducing vehicle power loss.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies related to the use of TMCC on fuel consumption have also been conducted. Warju et al [6] found that the use of metal catalytic converters in four-stroke engines did not significantly reduce fuel consumption. In fact, it resulted in an increase of 87%.…”
Section: Introductionmentioning
confidence: 99%